Hubungan Minat Belajar Siswa Menggunakan Aplikasi Welducation Terhadap Hasil Belajar Kelas XI Pada Mata Pelajaran SMAW SMK N 1 Sumatera Barat - Fanny Fadillah Ramadhan; Jasman Jasman; Bulkia Rahim; Andril Arafat (Jurnal Vokasi Mekanika (VoMek), 2025)
A person who is involved in the learning process regularly because of pleasure without external pressure is said to have an interest in learning. This interest is a relatively constant and enduring disposition, usually focused on one particular activity such as computers, science, athletics, music, or dancing. Based on observations during the Field Experience Practice (PPL), number of problems were found related to student interest in SMAW subjects. Some of these problems include student disinterest due to the use of less than optimal learning media and lecture methods that make students bored, fall asleep, or lose focus. Some students even refuse to complete the assigned tasks, indicating low interest in learning. Because interest in learning has a major influence on learning outcomes, it is important for students to understand school standards. This study uses a quantitative method to investigate the relationship between interest in learning and learning outcomes. This study collected and analyzed data using SPSS software. Subjects of the study were 25 grade XI Las students, and the independent variable was interest in learning as measured through the use of the Welducation application. The results of the analysis show that the average value of students' learning interest is 131.40 with a standard deviation of 15.047. Meanwhile, the average value of students' learning outcomes is 86.32 with a standard deviation of 0.985. The results of the hypothesis test show a significant relationship between learning interest and learning outcomes with a correlation coefficient of 0.899 and a significance value of 0.000.